From innovation to implementation : wearable data driven analytics and private health insurance in the United States - Soliño Fernández, Diego (2017)
The intent of this research was to define which wearable data-driven services addvalue to two key stakeholders in the healthcare system in the U.S.; consumers(insured or potential applicants) and private health insurers. In other words, theoverall goal of this master thesis was to discover new wearable data-driven analyticsor services that create a win-win scenario for consumers and private health insurersin the U.S., and, thus, could be implemented in the future.